The Impact of Electrode Configuration on Characteristics of Vacuum Discharge Plasma - 刘文正 张德金 孔飞 (Plasma science & technology, 2012)
Generation characteristics of vacuum discharge plasma are very important for the applied research of metal plasma. The vacuum discharge electrode configuration and the cathode material affect the generation characteristics of the metal plasma which consists of metal ions coming from cathode and generated by vacuum discharge. In this research, the generation characteristics of the metal plasma generated by vacuum discharge are discussed for four patterns of electrode configurations, i.e. cone-mesh electrode setup, cone-cross line electrode setup, cone-line electrode setup and cone-ring electrode setup. Characteristics of the metal plasma, such as elec- tron density, electron temperature, space potential, ion energy, are measured by the probe method for discussing the impacts of different electrode configurations on the density of generated metal plasma. Moreover, the diffusion velocities of the metal plasma are measured for cathode materials of Pb, Al, and Cu, respectively. The experimental results indicate that the plasma generated by the discharge of cone-ring electrode configuration possesses the maximum density and the metal plasma generated by the Al cathode possesses the fastest diffusion velocity and the highest kinetic energy.